The federal budget : politics, policy, process - Schick, Allen; LoStracco, Felix (Washington, D.C. : Brookings Institution Press, 2000)
"This book is an essential guide to understanding the federal budget process. Allen Schick brings together three critical elements of budget strategy: the political tactics and relationships that determine budgetary success or failure; the policy objectives pursued through the budget's revenue and spending proposals; and the rules and procedures that govern congressional and presidential action on these proposals." "Politics, policy, and process are integrated in a series of chapters that walk the reader through the many stages and complexities of federal budgeting. The author explains how budgeting works at each stage of executive and legislative action, from preparation of the president's budget through the appropriation and expenditure of funds. Throughout the book, he highlights documents actually used in federal budgeting." "The book provides an analysis of the early years of Bill Clinton's presidency, discusses budgetary actions already taken to deal with pressing social issues, and examines the outlook for the years ahead. Schick explains how the budget got so out of control and what can be done about it. He concludes with an assessment of the potential effects of current and proposed budgetary reforms."--Jacket
Conflict and resolution in federal budgeting -- The evolution of federal budgeting: from surplus to deficit to surplus -- The budget's shifting boundaries -- The political rules and arithmetic of budgeting -- The presidents' budget -- The congressional budget process -- Revenue legislation -- Authorizing legislation -- The appropriations process -- Managing federal expenditures -- The self-correcting budget process.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Budget -- United States; Budget process -- United States; Government spending policy -- United States; Budget -- États-Unis.; Dépenses publiques -- Politique gouvernementale -- États-Unis.; Processus budgétaire -- États-Unis.; MEDICAL -- Public Health; BUSINESS & ECONOMICS -- Public Finance; Government spending policy; Budget; Budget process; United States; Steuerpolitik; Fiskalpolitik; USA; Federale regering; Overheidsbegroting; Electronic book